Pre-treatment of Corcyra Cephalonica (Stainton) Eggs for Maximum Production of Wasps of Trichogramma Spp. - Yousuf, Mohammad; Sambath, S.; Chandra, Subhash (Indian Forester, 2012)
To achieve higher rate of parasitisation by egg parasitoids, Trichogramma spp., study was conducted to ensure 100 % mortality of the developing embryo inside the Corcyra cephalonica eggs and arresting the emergence of larvae by applying suitable chilling period to the host eggs. Three hours chilling of Corcyra cephalonica eggs at -8Â°C and RH 50 Â± 10% in refrigerator was found suitable for checking the embryonic development of Corcyra cephalonica eggs and also for maintaining the viability of eggs for parasitisation by Trichogramma spp. Parasitisation in three hours chilled eggs was recorded as high as 94.2% by T. brasiliensis, 93.4% by T.raoi and 92.6% by T.chilonis without hatching of any un-parasitised host egg.